Optimalisasi Manajemen Persediaan dengan Metode EOQ: Studi Kasus pada UMKM Lopek Bugi Kabupaten Kampar - Bamatraf, Lutfia; Afifah, Belia; Zulfikar, Zulfikar; Nurkholis, Nurkholis; Habibie, Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Lopek Bugi MSME in Kampar Regency, Riau, is one of the traditional regional food producers that faces challenges in raw material inventory management. The main problem is the imbalance between supply and demand, especially during periods of high demand, which often leads to raw material shortages and loss of sales potential. This study aims to optimize inventory management using the Economic Order Quantity (EOQ) method. A quantitative approach with case studies is used in this study, with data collected through direct observation, interviews, and historical documentation. The results of the study indicate that the EOQ method is able to determine the optimal order quantity that minimizes total inventory costs. In addition, this method helps in determining the reorder point (ROP) and safety stock to prevent stock shortages and anticipate demand fluctuations. This study provides practical benefits for Lopek Bugi MSME in managing its inventory efficiently and economically. The results of this study are expected to be a reference for the development of local government policies in supporting the optimization of MSME inventory management.